Report of Barley Variety Trials Crop 1996 and 1997: Submitted on behalf of the EBC Barley & Malt Committee (BrewingScience, 1998)
The EBC Barley & Malt Committee is organizing barley variety trials in four regions in Europe: North, West, Central and South. Region North includes Denmark, Finland, Sweden and Estonia; Retin West includes Great Britain, France, BElgium and The Netherlands; Region Central includes Germany, Hungary, the Czech Republic, the Slovak Republic and Austria; Region South includes Portugal, Spain, Italy and Bulgaria. The barley varieties tested are selected by the Committee using transparant parameters described in the Results Field Trials 1996, published in July 1997. Details of growing areas, analytical parameters of both barley and corresponding malt are available through this report. Copies of the Report as well as more detailed information can be obtained through the national members of the Committee. The EBC Barley & Malt committee is responsible for the organisation of the barley variety trials and for the quality of the resulting data, but not for the evaluation of the quality of the tested varieties. Rating of the barley varieties tested in the four regions is the reponsibility of each individual company or institute.